Low Bone Mineral Density in Hemophiliacs - Gebetsberger, Jennifer; Schirmer, Michael; Wurzer, Walter J.; Streif, Werner (Frontiers in Medicine, 2022)
Objective To review the current knowledge on bone health in patients with hemophilia A and the underlying pathogenetic mechanisms. Data Sources Original research articles, meta-analyses, and scientific reviews. Data Synthesis Already in childhood, patients with hemophilia A are prone to low bone mineral density, leading to osteopenia and/or osteoporosis. Initially associated with the life style of hemophilia, today we are faced with accumulating evidence that coagulation factor VIII is involved directly or indirectly in bone physiology. Conclusion Understanding the role of factor VIII and the mechanisms of decreased bone mineral density in hemophilia A is critically important, especially as non-factor replacement therapies are available, and treatment decisions potentially impact bone health.